The Effect of Competence and Organizational Culture on Health Workers' Performance through Work Motivation at the Primary Clinic of Indonesian Medical Partners - Hairia Yazid; Munawaroh (Journal of Islamic Studies & Social Science, 2024)
This study aims to 1) analyze the influence of competence and organizational culture on the work motivation of the health worker team. 2) analyze the influence of competence and organizational culture on the performance of the health worker team. 3) analyze the effect of motivation on the performance of a team of health workers at the Primary Clinic of Mitra Medis Indonesia. 4) analyze the influence of competence on the performance of the health worker team through motivation. 5) analyzing the influence of organizational culture on the performance of the health worker team through motivation. The results showed that: 1) there is a positive and significant influence both partially and simultaneously between competence and organizational culture on the work motivation of the health worker team at the Pratama Mitra Medis Indonesia Clinic. 2) there is a positive and significant influence both partially and simultaneously between competence and organizational culture on the performance of the health worker team at the Pratama Clinic of Mitra Medis Indonesia. 3). there is a positive and significant influence between motivation on the performance of the health worker team at the Pratama Mitra Medis Indonesia Clinic. 4) there is an influence of competence on the performance of the health worker team through motivation at the Pratama Mitra Medis Indonesia Clinic. 5) there is an influence of organizational culture on the performance of the health worker team through motivation. This also states that the work motivation factor functions or acts as an intervening variable.